Optimization of lignin peroxidase production and stability by Phanerochaete chrysosporium using sewage-treatment-plant sludge as substrate in a stirred-tank bioreactor - Alam, Md. Zahangir; Mansor, Mariatul F.; Khan Chowdhury, Ahmed Jalal (Springer, 2009)
A laboratory-scale study was carried out to produce lignin peroxidase (ligninase) by white rot fungus (Phanerochaete chrysosporium) using sewage-treatmentplant (STP) sludge as the major substrate. The optimization was done using full-factorial design (FFD) with agitation and aeration as the two parameters. Nine experiments indicated by the FFD were fermented in a stirred-tank bioreactor for 3 days. A second-order quadratic model was developed using the regression analysis of the experimental results with the linear, quadratic, and interaction effects of the parameters. Analysis of variance (ANOVA) showed a high coefficient of determination (R2) value of 0.972, thus indicating a satisfactory fit of the quadratic model with the experimental data. Using statistical analysis, the optimum aeration and agitation rates were determined to be 2.0 vvm and 200 rpm, respectively, with a maximum activity of 225 U l-1 in the first 3 days of fermentation. The validation experiment showed the maximum activity of lignin peroxidase was 744 U l-1 after 5 days of fermentation. The results for the tests of the stability of lignin peroxidase showed that the activity was more than 80% of the maximum for the first 12 h of incubation at an optimum pH of 5 and temperature of 55C.